Polymorphism in Genes Encoding HSP40 Family Proteins is Associated with Ischemic Stroke Risk and Brain Infarct Size: A Pilot Study - Ksenia A. Kobzeva; Denis E. Gurtovoy; Alexey V. Polonikov; Vladimir M. Pokrovsky; Evgeny A. Patrakhanov; Olga Y. Bushueva (Journal of Integrative Neuroscience)
Background: Heat shock proteins (HSPs) play a critical role in the molecular mechanisms of ischemic stroke (IS). A possible role for HSP40 family proteins in atherosclerosis progression has already been revealed; however, to date, molecular genetic studies on the involvement of genes encoding proteins of the HSP40 family in IS have not yet been carried out. Aim: We sought to determine whether nine single nucleotide polymorphisms (SNPs) in genes encoding HSP40 family proteins (DNAJB1, DNAJB2, DNAJA1, DNAJA2, DNAJA3 and DNAJC7) are associated with the risk and clinical features of IS. Methods: Using TaqMan-based polymerase chain reaction (PCR) and the MassArray-4 system, DNA samples of 2551 Russians — 1306 IS patients and 1245 healthy individuals — were genotyped. Results: SNP rs2034598 DNAJA2 decreased the risk of IS exclusively in male patients (odds ratio = 0.81, 95% confidence interval 0.78–0.98, p = 0.028); rs7189628 DNAJA2 increased the brain infarct size (p = 0.04); and rs6500605 DNAJA3 lowered the age of onset of IS (p = 0.03). SNPs rs10448231 DNAJA1, rs7189628 DNAJA2, rs4926222 DNAJB1 and rs2034598 DNAJA2 were involved in the strongest epistatic interactions linked to IS; SNP rs10448231 DNAJA1 is characterised by the most essential mono-effect (2.96% of IS entropy); all of the top SNP–SNP interaction models included the pairwise combination rs7189628 DNAJA2×rs4926222 DNAJB1, which was found to be a key factor determining susceptibility to IS. In interactions with the studied SNPs, smoking was found to have multidirectional effects (synergism, antagonism or additive effect) and the strongest mono-effect (3.47% of IS entropy), exceeding the mono-effects of rs6500605 DNAJA3, rs10448231 DNAJA1, rs2034598 DNAJA2, rs7189628 DNAJA2 and rs4926222 DNAJB1, involved in the best G×E models and determining 0.03%–0.73% of IS entropy. Conclusions: We are the first to discover polymorphisms in genes encoding HSP40 family proteins as a major risk factor for IS and its clinical manifestations. The comprehensive bioinformatics analysis revealed molecular mechanisms, underscoring their significance in the pathogenesis of IS, primarily reflecting the regulation of heat stress, proteostasis and cellular signalling.